Приведи к подобным слагаемам
7(х-3)-4(х-5)+8
-6(а-b)-2(3b+2a)-23a
3.6(2y-1)-4(3y-1)-5.5(x+3)+7(x+y-5)
2.6(4-2b)-7.6(a-2)-5(6b-a+20)
реши уравнение
8x-3x-6x= - 7.3
3x-2.5x+3+x - 1.3 = 0
x-4.5x+3x-4.7+5.8 = 0
-2x +5.5x-4.1+8 - 0.5x = 0

2

Ответы и объяснения

2014-02-22T16:27:52+04:00
Первое: 7х-21-4х+20+8
3х=7
второе: -6а+6b-6b-4a-23a
-33a
2014-02-22T17:50:57+04:00
3.6(2y-1)-4(3y-1)-5.5(x+3)+7(x+y-5)=7,2y-3,6-12y+4-5,5x-16,5+7x+7y-35=2,2y-51,1+1,5x
 -----------------------------------------------------------------------------------------------------------------------------                                                                                                                 2.6(4-2b)-7.6(a-2)-5(6b-a+20) =10,4-5,2b-7,6a+15,2-30b+5a-100=-74,4-35,2b-2,6a
---------------------------------------------------------------------------------------------------------------------
8x-3x-6x= - 7.3
x=7,3

3x-2.5x+3+x - 1.3 = 0
1,5x=-1,7
x=-1 2/15

x-4.5x+3x-4.7+5.8 = 0
0,5x=4,7-5,8
0,5x=-1,1
x=-2,2


-2x +5.5x-4.1+8 - 0.5x = 0
3x=4,1-8
3x=-3,9
x=-1,3